2010
DOI: 10.1007/s10072-010-0360-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and [11C]-CFT PET analysis of PARK2, PARK6, PARK7-linked autosomal recessive early onset Parkinsonism

Abstract: Mutations in the Parkin, PINK1, and DJ-1 genes can cause autosomal recessive early onset Parkinsonism. We studied three families with the mutations of the Parkin, PINK1 and DJ-1 genes, respectively, with a dopamine transporter ligand [(11)C]-CFT positron emission tomography. A marked bilaterally and dissymmetrically decrement of [(11)C]-CFT uptake was found in all these patients, and putamen as well as caudate nucleus was affected. We also found asymptomatic Parkin and PINK1 heterozygotes showed a mild but sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Mutations to the Pink1 (PTEN-induced putative kinase) gene in humans have been associated with both an autosomal recessive, early-onset form of PD as well sporadic cases [2325]. Evidence indicates that associated deficits within the human Pink1 genetic form of PD may also include voice and swallow deficits similar to idiopathic PD, though this has not been well characterized in terms of onset, progression, and severity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations to the Pink1 (PTEN-induced putative kinase) gene in humans have been associated with both an autosomal recessive, early-onset form of PD as well sporadic cases [2325]. Evidence indicates that associated deficits within the human Pink1 genetic form of PD may also include voice and swallow deficits similar to idiopathic PD, though this has not been well characterized in terms of onset, progression, and severity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Rats in this specific genetic model express a form of PD that is due to the complete knockout of the PINK1 gene, loss of function mutation, which is related to the PARK6 phenotype of human familial PD. In humans, PINK1 genetic variants contribute to early onset of PD with progressive deficits over time, extensive nigrostriatal dopamine depletion in the late stages of the disease, as well as other motor and non-motor deficits [2426]. PINK1 −/− rats have comparable symptom profiles to sporadic PD patients; specifically, this model exhibits significant vocalization deficits beginning at 2 months (mo) of age (decreased vocal loudness) that persist and progress (decreased peak frequency and bandwidth) at 4, 6 and 8 mo of age [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in these genes are a common cause of early-onset Parkinson's disease (Klein et al ., 2007). While heterozygous carriers of a single Parkin or PINK1 mutation are usually free of clinical motor symptoms, it is now well established that these asymptomatic mutation carriers show a significant reduction of 18 F-fluoro- l -DOPA metabolism in the putamen (Hilker et al ., 2001, 2002; Khan et al ., 2002, 2005; Scherfler et al ., 2004; Pavese et al ., 2009; Guo et al ., 2011). Two recent functional MRI studies have indicated that asymptomatic Parkin and PINK1 mutation carriers show a stronger increase of cortical motor-related activity during execution of self-initiated movements than non-mutation carriers (Buhmann et al ., 2005; van Nuenen et al ., 2009 a ).…”
Section: Introductionmentioning
confidence: 99%